Development of Dioxin Data Base System and Analysis of Dioxin Pollution - SAKURAGI, Kenji; MATSUEDA, Takahiko; KUROKAWA, Yoichi; IWAMOTO, Shinji; OHNO, Kenji; TOBIISHI, Kazuhiro (Journal of Environmental Chemistry, 2004)
The data base system was developed to understand the pollution of dioxin. This data base is composed of 118 isomer concentrations, TEQ concentrations and congener concentrations with sampling date, sampling site, their position informations etc. We accumulated over 700 samples in this data base by past continuous survey. This data base can show isomer pattern graph, congener pattern graph, radar chart of selected isomers and TEQ composition graph. It also can make distribution map of TEQ concentrations and some isomers. Statistical analysis such as principal component analysis and multiple regression analysis is available to estimate dioxin sources. Source apportionment of dioxin is calculated by Chemical Mass Balance (CMB) method. Based on the data base, it becomes clear that air is mainly polluted by emission from waste incinerator, while river water and soil are mainly polluted by impurities in herbicide such as pentachlorophenol (PCP) and chloronitrophen (CNP) . Source contribution of dioxin was predicted by multiple regression analysis and CMB method. These results indicate that waste incinerator accounts for over 60% of air samples, on the other hand, herbicide (PCP, CNP) accounts for over 60% of river water and soil samples.